DETERMINANT OF GOVERNMENT BANK PERFORMANCE THROUGH NIM AS INTERVENING - Sari, Laynita; Nandan Limakrisna; Renil Septiano (Dinasti International Journal of Economics, Finance & Accounting, 2020)
A government bank is a bank in which most of its shares are owned by the government. The government bank comprises four banks namely Bank Rakyat Indonesia, Bank Negara Indonesia, Bank Mandiri, and Bank Tabungan Negara. One ratio used to assess a bank’s performance is the Return on Asset ratio. Each bank will try to keep its Return on Asset ratio consistently rising. But the phenomenon is that the Government Bank’s Return on Asset ratio fluctuated from 2014 to 2019. I will therefore examine the factors that affect the ratio of Return on Assets to government banks. In this study, the ratio used was Non Performing Loan as independent variable, Net Interest Margin as intervening variable and Return on Asset on dependent variable. The result that the Net Interest Margin variable does not mediate the relationship between Non Performing Loan and Return on Asset